Science communication is needed to inform risk perception and action of stakeholders. (1st March 2020) - Requier, Fabrice; Fournier, Alice; Rome, Quentin; Darrouzet, Eric
Abstract: Stakeholders are critical environmental managers in human-dominated landscapes. In some contexts, stakeholders can be forced to personally act following their own observations and risk perception instead of science recommendation. In particular, biological invasions need rapid control actions to reduce potential socio-ecological impacts, while science-based risk assessments are rather complex and time-delayed. Although they can lead to important detrimental effects on biodiversity, potential time-delayed disconnections between stakeholders' action and science recommendations are rarely studied. Using the case study of western European beekeepers controlling the invasive Asian hornet Vespa velutina nigrithorax for its suspected impact on honey bee colonies, we analysed mechanisms underlying personal actions of stakeholders and how they evolved in science disconnection. Personal actions of stakeholders were causal-effect linked with their risk observation but disconnected to time-delayed science predictions and recommendations. Unfortunately, these science-disconnected actions also led to dramatic impacts on numerous species of the local entomofauna. These results highlight the need to improve mutual risk communication between science and action in the early-stages of management plans to improve the sustainably of stakeholders' practices. Highlights: Current global changes can lead to time lags between science and action. We analyse stakeholder actions and how they evolved in science disconnection. Stakeholder actions are disconnected to time-delayed science recommendations. Science-disconnected actions impact local biodiversity. Improving risk communication to biological invasion is urgently required.